Proteome Kinetics: Coupling the Administration of Stable Isotopes with Mass Spectrometry-Based Analyses - Previs, Stephen F.; Zhou, Haihong; Wang, Sheng-Ping; Herath, Kithsiri; Johns, Douglas G.; Roddy, Thomas P.; Kasumov, Takhar; Hubbard, Brian K. (IntechOpen, 2012)
None